2011
DOI: 10.1002/alr.20043
|View full text |Cite
|
Sign up to set email alerts
|

Correlating matrix metalloproteinase‐9 sinus secretion levels with tissue biopsy levels

Abstract: Secretion collection can replace tissue biopsy for MMP-9 determinations, reducing morbidity. Furthermore, secretion collection allows sequential sampling from the same location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Nasal secretions have generally been studied in allergic rhinitis, with limited data available for CRS. The only direct connection between nasal secretions and corresponding sinus tissue levels has been shown for matrix metalloproteinase‐9 by enzyme‐linked immunosorbent assay from ethmoid sinus biopsies and secretions . The authors found a significant correlation between tissue and secretion levels ( P = 0.0033, r = 0.52) among the 30 patients with CRS studied but did not use tissue sample weight or protein content to standardize sample size, thus introducing a potentially confounding factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasal secretions have generally been studied in allergic rhinitis, with limited data available for CRS. The only direct connection between nasal secretions and corresponding sinus tissue levels has been shown for matrix metalloproteinase‐9 by enzyme‐linked immunosorbent assay from ethmoid sinus biopsies and secretions . The authors found a significant correlation between tissue and secretion levels ( P = 0.0033, r = 0.52) among the 30 patients with CRS studied but did not use tissue sample weight or protein content to standardize sample size, thus introducing a potentially confounding factor.…”
Section: Discussionmentioning
confidence: 99%
“…The only direct connection between nasal secretions and corresponding sinus tissue levels has been shown for matrix metalloproteinase-9 by enzyme-linked immunosorbent assay from ethmoid sinus biopsies and secretions. 13 The authors found a significant correlation between tissue and secretion levels (P 5 0.0033, r 5 0.52) among the 30 patients with CRS studied but did not use tissue sample weight or protein content to standardize sample size, thus introducing a potentially confounding factor. The current study found significant correlations between tissue and sinus secretion cytokine levels for five of the six cytokines within the detectable ranges of the assay.…”
Section: Specimen Collection Technique and Cytokine Correlationmentioning
confidence: 98%
“…Scientists have shown that a simple secretion collection can replace tissue biopsy for MMP‐9 determinations, reducing morbidity. Furthermore, secretion collection allows sequential sampling from the same location (Wilson et al, ). As MMP‐9 is involved in the breakdown of the extracellular matrix, it is considered a hallmark in airway remodeling.…”
Section: Matrix Metalloproteinase‐9mentioning
confidence: 99%
“…When interpreting the results, it is important to notice that we evaluated secreted forms of MMPs and TIMPs, whereas most studies in CRS have either analyzed tissue homogenates or used immunohistochemistry, making direct comparisons difficult. Even though MMP‐9 levels in nasal secretions have been shown to reflect MMP‐9 levels in tissue at least moderately, there are no studies concerning MMP‐8 and TIMPs on this matter . Polymorphonuclear leukocytes are an important source of MMP‐8 and MMP‐9, thus the higher leukocyte count in the inflamed mucosa may explain the increased MMP levels in tissue homogenates in CRSwNP.…”
Section: Discussionmentioning
confidence: 99%